Professional risk in anesthesiology. - Marlene Alejo Aris; Evangelina Dávila Cabo; Carlos M Hernández DÁvila; Madga Robaina (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2006)
Working with the profession is an exercise that implies a risk that is related to the characteristics of the job, that is why anaesthesiology can cause diseases due to the exposition to the stress of surgical and urgency environment, inhalation and contact with anaesthetic teratogenic and carciogenic agents and to the eventual exposition to iozining radiation among other dangers.